Analisis Kualitas Website pada Akper Pembina Palembang Menggunakan Metode Webqual - Ayu, Sri Rahayu (Jurnal Ilmiah Binary STMIK Bina Nusantara Jaya, 2024)
AKPER Pembina Palembang website which is located ( www.akperpembina.ac.id ) was built with the aim of organizing academic data. This study aims to determine the difference between the perceptions and expectations of website users, in this case the students of AKPER Pembina Palembang, as measured by the WebQual approach, which is one of the techniques for measuring the quality of websites based on user perceptions. The WebQual method used in this study is a modified version of the WebQual by adding a user interface quality dimension with the three main dimensions of WebQual, namely Usability, Information Quality, and Service Interaction Quality. The analysis technique uses Difference Analysis (t test) and Importance Performance Analysis (IPA). The results of the study prove that there is a difference between the perceptions and expectations of students on each of the dimensions of the quality of the website, this indicates that the quality level of the AKPER Pembina Palembang website is not in accordance with student expectations. The results of the mapping in the Cartesian diagram are expected to provide feedback for the management of the website in formulating strategies to improve the quality of the AKPER Pembina Palembang website.Keywords: Website Quality, Perception, Expectations, WebQual Importance Performance Analysis (IPA), Difference Analysis.